Experiences of Urban Australian Indigenous peer Mentors in a Non-Communicable Disease Prevention Program. (December 2016) - Adams, Karen; Browne, Jennifer; Palermo, Claire; Radford, Gail
This paper describes urban Indigenous Australian experiences of a peer mentor program (PMP) aiming to reduce non-communicable disease (NCD) risks and discusses its implications for future policy and practice. Much of the inequitable mortality for Indigenous Australians is related to NCD incidence. Using a qualitative approach the study reported here explored 21 people's experiences as peer mentors in an NCD risk reduction PMP, which took place between 2009 and 2011. Four key themes were identified, including community networks, collective wellbeing, skills development and problem solving, and sustainability. The PMP allowed for inclusiveness of individual strengths, diversity and cultural knowledge. Formal networks provided sustainability and information while peer informal networks provided increased participation, knowledge dissemination, practice of health-promoting skills and provision of support. Inclusion of collective cultural elements, such as connections to Elders, families, children and Country were particularly important for the peer mentors in this study.